Decadal stability in top predator habitat preferences in the Bay of Biscay. (September 2018) - Lambert, C.; Authier, M.; Doray, M.; Dorémus, G.; Spitz, J.; Ridoux, V.
Highlights: Concurrent sampling of predators and habitat unveiled their relationships in time. PCA on environmental variables identified 3 main habitats used by predators. Predators exhibited various habitat preferences specificity and stability in time. Narrower habitat preferences paired with stronger stability among years. Wider habitat preferences paired with higher variability among years. Abstract: Most oceanographic systems, especially shelf ecosystems, are characterised by interannual variability in the timing, extent and intensity of their seasonal patterns. Such interannual variations have important consequences on top predator habitat preferences. Capitalising on oceanographic surveys performed every spring since 2004 in the Bay of Biscay (BoB), this study explored interannual variations in habitat preferences exhibited by five mobile top predator species: bottlenose and common dolphins, auks, fulmars and northern gannets. We expected to find species with similar habitat preferences every year or species exhibiting important variability in their habitat preferences. First, we identified with a Principal Component Analysis (PCA) three different habitats of varying extent depending on year: river plumes, central shelf waters and shelf edge. Second, the Principal Components were used to explore the habitat preferences of predators through Generalized Additive Models. We fitted two kinds of models, using and not using the year as an interaction term, to test whether habitat preferences changed across years. Our results showed a range of habitat strategies based on the specificity and stability of species preferences. Species exhibiting narrower habitat preferences also exhibited stronger stability in their preferences among years while the species with wider habitat preferences exhibited higher variability among years. The target habitats differed across studied species, with bottlenose dolphins targeting the shelf edge exclusively, auks preferring river plumes, fulmars exhibiting a gradual preference from the shelf edge to river plumes and gannets being present in any of the three habitats. In contrast, the habitat preferences of common dolphins, the most sighted cetacean species in the BoB, could not be reliably inferred.